Effect of different spray tips and pressures on the application of calcium carbonate in conilon coffee seedlings - Soela, Débora Moro; Vitória, Edney Leandro da; Falqueto, Antelmo Ralph; Freitas, Ismael Lourenço de Jesus; Braga, Priscila Conceição Souza; Simon, Cátia Aparecida (Brazilian Journal of Production Engineering, 2021)
The efficient application of agricultural products depends on a number of factors, including the correct choice of spray tip and working pressure. The objective of this study was to determine which set of spray tips and working pressure provide the best coverage in conilon coffee seedlings. The experiment was conducted in a randomized block design in a factorial scheme 3 x 4 three spray tips (BD 01, MGA 60º 1.0, MCP 1.5), four spray pressures (206, 275, 344 and 413 kPa), four replications and four plants in each plot. The application rate was the same in all treatments, 100 L ha-1 and a dose of 2 L ha-1 of the product used. The first application of the product was carried out inside the nursery, and the subsequent ones, in the field after planting the seedlings, with an interval of seven days between them. Droplet spectrum analyzes were performed, in which the parameters of diameter of the volumetric median (DMV), droplet density (DEN) and cover (COB) were evaluated. The pressure at all ends influenced the coverage variable, as the pressure increases, the better the percentage of coverage. The empty cone tip MGA 60ª at a pressure of 413 kPa promoted the best percentage of coverage of the evaluated product, therefore, the best option for application.